Pengembangan Game Edukasi Wordwall untuk Meningkatkan Minat Belajar Siswa dalam Mata Pelajaran Sejarah Kebudayaan Islam di MTS al-Asy’ariyah Banjarsari - Kristina Putri Anggraeni; Khoirun Nisa; Wahyudi Wahyudi (Lembaga Yasin AlSys, 2026)
The development of interactive learning media is necessary to increase students’ interest and understanding in the subject of Islamic Cultural History (SKI), particularly through the use of educational game-based technology. This study aimed to develop interactive learning media based on the Wordwall game to increase students’ interest and understanding in the SKI subject at MTs Al-Asy’ariyah Banjarsari. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of needs analysis, design, development, implementation, and evaluation. The product developed was an SKIPlay educational game containing interactive quizzes and a “balloon pop” game aligned with the learning outcomes of the Kurikulum Merdeka. The validation results showed that the developed media met the feasibility criteria, with a media expert assessment score of 92.5% in the highly valid category and a material expert assessment score of 100% in the highly valid category. A limited trial involving 28 eighth-grade students showed a student response score of 86.21%, indicating that the Wordwall media was considered engaging, easy to use, and helpful in understanding SKI material. The paired sample t-test obtained a significance value of 0.00 < 0.05, indicating a significant improvement after the use of the media. In addition, the N-Gain score of 75.26% was in the moderately effective category. These findings confirm that the Wordwall media based on the SKIPlay educational game is feasible and moderately effective for increasing students’ learning interest and understanding in SKI learning.